Phytoplankton communities as indicators of the trophic status of Playas del Este, La Habana, Cuba - Bustamante-López, Claudia (2016)
The analysis of phytoplankton in coastal ecosystems helps predict changes in trophic status. This paper is aimed at characterizing the structure and composition of phytoplankton communities as indicators of trophic state and describing inter-annual and spatial variations of phytoplankton related to abiotic factors in Playas del Este. Eleven stations were located and the phytoplankton structure was determined from samples of network and bottle phytoplankton. Flagellates and Navicula genus held a constant spatiotemporal presence in the sampled period. Other genus and species that also showed high frequency in February and July 2011 and February and August 2012 were: Scrippsiella trochoidea and Gymnodinium sp. Potentially harmful organisms were also detected such as Oscillatoria sp., S. trochoidea, Akashiwo sanguinea, Alexandrium sp. and Gambierdiscus sp., mainly in the month of February for both years. The contribution by groups to the phytoplankton community in both years showed predominance of flagellates (over 50%) and a small contribution of diatoms and dinoflagellates in the total community (less than 25%). The availability of nitrogen and phosphor is the main element affecting the development of phytoplankton. The Tropicoco, Tarará, and Bacuranao stations have the highest phytoplankton density during both years. Insignificant differences were detected between the 2011 (R = 0.465) and 2012 (R = 0.212) seasons and climate stations for each period (R = 0.324). The trophic status of waters was classified as oligo-mesotrophic for 2011 and 2012.